A CONVERSATION WITH DONALD SNOWDON - Anderson, Gary (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1981)
To most of us curriculum refers to the educational activities of school systems. There is, however, another broader field of curriculum which involves informal learning for people of all ages, learning about all types of subjects. The people involved in this important work are generally not academic scholars, rather they are field-based practitioners who spend their time getting tangible results. They seldom write articles for academic publications. For this reason, we present the work of Donald Snowdon not in the form of an academic article but rather as an interview, which through its medium communicates well the messages of informal curriculum building. Snowdon himself developed techniques of community development known as the Challenge for Change Program, which was sponsored in its early days by the National Film Board of Canada. It involves using film and videotape to help people in their own self development. RÉSUMÉ Pour la majorité d’entre nous, les programmes évoquent les activités pédagogiques des systèmes scolaires. Il existe pourtant un éventail de programmes beaucoup plus vaste destinés aux gens de tous les âges qui étudient toutes sortes de sujets. Les gens qui y participent ne sont généralement pas des universitaires mais plutôt des praticiens qui passent leur temps à produire des résultats tangibles. Il leur arrive rarement d’écrire des articles pour des revues savantes. C’est pourquoi nous présentons le travail de Donald Snowdon non pas sous la forme d’un article savant mais sous celle d’une entrevue qui transmet fort bien les messages relatifs à l’élaboration informelle des programmes. Snowdon a lui-même mis au point les techniques de développement communautaire connues sous le nom de "Programme de tentatives de changement", lequel a été parrainé à ses débuts par l’Office national du Film du Canada. Ce programme fait appel aux films et aux bandes vidéo pour aider les gens à réaliser leur propre développement.